2020
DOI: 10.3390/nu12103056
|View full text |Cite
|
Sign up to set email alerts
|

A Partially Hydrolyzed Whey Infant Formula Supports Appropriate Growth: A Randomized Controlled Non-Inferiority Trial

Abstract: The aim of the current study was to investigate the effects of a partially hydrolyzed whey infant formula (PHF) on growth in healthy term infants as compared to a standard infant formula with intact protein (IPF). In a double-blind, non-inferiority, randomized controlled trial, a total of 163 healthy formula-fed infants, 55–80 days old, were recruited and randomly allocated to either the PHF (test) or the IPF (control) group. They were followed up for three months during which they were evaluated monthly on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The current results for growth outcomes, including the primary outcome of daily weight gain, are in agreement with findings from previous studies. First and foremost, similar results were found in the study by Karaglani et al, which assessed the effects on growth parameters of a pHF compared to an IPF in 163 healthy formula-fed infants over a period of three months (19). Similarly, other previous studies investigating the effects of different pHFs on growth indices of infants as compared to intact protein-based formulas or breast milk have found no differences among the study groups (20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 82%
“…The current results for growth outcomes, including the primary outcome of daily weight gain, are in agreement with findings from previous studies. First and foremost, similar results were found in the study by Karaglani et al, which assessed the effects on growth parameters of a pHF compared to an IPF in 163 healthy formula-fed infants over a period of three months (19). Similarly, other previous studies investigating the effects of different pHFs on growth indices of infants as compared to intact protein-based formulas or breast milk have found no differences among the study groups (20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 82%
“…(2011) [ 10 ], infants fed an HP formula had significantly lower weight-for-length z-scores compared to IP formula-fed infants across ages 2.5 to 7.5 months. As discussed by others [ 9 ], this difference may be due to the lower food consumption observed in this study in the HP formula group. HP formulae contain peptides that can display a bitter taste [ 24 ] and might also lead to more rapid satiation [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 46%
“…The findings of this study are consistent with observations reported in other publications. Karaglani et al (2020) [ 9 ], Picaud et al (2020) [ 4 ], and Otten et al (2023) [ 21 ] demonstrated in three randomized controlled studies comparable growth between infants fed a partially or extensively hydrolyzed whey-based formula and infants fed an intact cow’s milk protein formula during the first 4 to 5 months of life. Similar results with no difference in growth characteristics between HP and IP formulae were observed by Wu et al (2017) [ 22 ] in healthy term infants from enrolment to 7 and 13 weeks of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations